PENGARUH PROGRAM PENDIDIKAN PELATIHAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA TENAGA PENYULUH KELUARGA BERENCANA (KB) DI PROVINSI RIAU (STUDI KASUS PADA KABUPATEN PELALAWAN, KABUPATEN SIAK DAN KABUPATEN INDRAGIRI HULU) - wulandari, Desy; Hendriani, Susi (Jurnal Tepak Manajemen Bisnis, 2014)
Abstract. The objective of this research is to analize the effect of the education and training programm, motivation dan job environment again the performance of fieldworkers for family planning in Riau Province. This research takes 3 sample of r egency, that they are Pelalawan Regency, Siak Regency and Indragiri Hulu Regency . From above formula we can see that the regression coeffisien for three independent variables have a positive effect again dependent variables (perfrmance of fieldworkers of family planning in Riau Province). The number of effect contributed by the education and training programm, motivation and job environment again the performance of fieldworkers of family planning in Riau Province can be seen from determinated coefficient (R2) and the figure is 0,465 or 45,5%. While closed relationship between independent variables and dependent variable is indicated by the figure coefficient correlation (R) is 0,682.The parcial test indicated that the biggest tratio is found on variable the education and training programm (X1) the tratio= 4,598 > ttabel= 1,662 with the r 2 = 44,0%. This result indicates that the education and training programm has the main factor again performance of fieldworkers of family planning in Riau Province.Keywords : the education and training programm, motivation, job environment, performance of fieldworkers.